Habits of affluence: unfeeling, enactivism and the ecological crisis of capitalism - Jan Slaby (Mind & Society, 2024)
In this text, I discuss the role that a range of habits in affluent societies play in upholding as well as masking an unsustainable status quo. I show that enactivism, as a philosophical approach to the embodied and embedded mind, offers resources for bringing into focus and critically interrogating such habits of affluence and the environments enabling them. I do this in the context of a critical theory of the unfelt in society : the systematic production of lacunae of emotive concern in social collectives. The lack of proportionate affective and practical responses to the ecological crisis epitomizes this. The article starts with considerations on societal unfeeling, then reviews key elements of enactive approaches to habit, before a fuller picture of habits of affluence is developed, informed by Brand's and Wissen's concept of the imperial mode of living . Finally, two dimensions of habits of affluence are discussed in some detail, which will help flesh out a thematically expanded, politically engaged version of enactivism.
Keywords: 300; Affect; Emotion; Enactivism; Habit; The imperial mode of living; Social niche